Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1016/s0925-4439(02)00156-4
|View full text |Cite
|
Sign up to set email alerts
|

The peak height ratio of S-sulfonated transthyretin and other oxidized isoforms as a marker for molybdenum cofactor deficiency, measured by electrospray ionization mass spectrometry

Abstract: Molybdenum cofactor deficiency is a fatal neurological disorder, which follows an autosomal-recessive trait and is characterized by combined deficiency of the enzyme, sulfite oxidase, xanthine dehydrogenase and aldehyde oxidase. Early detection of molybdenum cofactor-deficient patients is essential for their proper care and genetic counseling of families at risk. We demonstrate the use of S-sulfonated transthyretin (TTR) as a marker for molybdenum cofactor deficiency. Plasma or sera obtained from 4 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
4
32
0
Order By: Relevance
“…Major spots in Fig. 1 were identified [7,23], but the low-molecular-mass proteins are not well resolved compared to the mass spectrometric results of the corresponding proteins [15][16][17][19][20][21]. The reported MALDI- MS spectra showed that the plasma lipoproteins have been dissociated into their component apolipoproteins, possibly because of the sample treatment with a matrix solution which contains TFA and ACN [19].…”
Section: Maldi-tof-ms Of Human Plasma Treated With Dttmentioning
confidence: 99%
See 3 more Smart Citations
“…Major spots in Fig. 1 were identified [7,23], but the low-molecular-mass proteins are not well resolved compared to the mass spectrometric results of the corresponding proteins [15][16][17][19][20][21]. The reported MALDI- MS spectra showed that the plasma lipoproteins have been dissociated into their component apolipoproteins, possibly because of the sample treatment with a matrix solution which contains TFA and ACN [19].…”
Section: Maldi-tof-ms Of Human Plasma Treated With Dttmentioning
confidence: 99%
“…In this study, seven isoform of TTR are detected by MALDI-TOF-MS. The prominent peak 29 was assigned to be the unmodified TTR and peak 30 was an isoform sulfonated at Cys10 [14,15]. Peaks 31, 32, and 35 were assigned to be TTR-cysteinylated, TTR conjugated with cysteinylglycine, and TTR conjugated with glutathione, all at Cys10 residue [35].…”
Section: Transthyretinmentioning
confidence: 99%
See 2 more Smart Citations
“…Wada et al (12 ) were the first to perform the analysis of tryptic fragments of TTR by MS. This spawned several other mass spectrometric approaches to analyze and catalog TTR for any variations that differ from the wild-type amino acid sequence (6,(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%